A Southern Moderate in Radical Times : Henry Washington Hilliard, 1808-1892 - Durham, David I. (Book collections on Project MUSE., 2008)
In A Southern Moderate in Radical Times, David I. Durham offers a comprehensive and critical appraisal of one of the South's famous dissenters. Against the backdrop of one of the most turbulent periods in American history, he explores the ideological and political journey of Henry Washington Hilliard (1808-1892), a southern politician whose opposition to secession placed him at odds with many of his peers in the South's elite class. Durham weaves threads of American legal, social, and diplomatic history to tell the story of this fascinating man who, living during a time of unrestrained destruc.